Experimental Investigation of Dispersant on Dynamics of Impact of Al2O3 Nanofluid Droplet - Dandan Liang; Ruichao Guo; Zichun Sun; Haizhen Zhao; Guohua Qin; Yongxin Zhang (Nanomaterials)
Spray cooling, of which the essence is droplet impacting, is an efficient thermal management technique for dense electronic components in unmanned aerial vehicles (UAVs). Nanofluids are pointed as promising cooling dispersions. Since the nanofluids are unstable, a dispersant could be added to the fluid. However, the added dispersant may influence the droplet, thereby impacting behaviors. In this work, the effects of dispersant on the nanofluid droplet-impacting dynamics are studied experimentally. The base fluid is deionized water (DI water), and Al2O3 is the selected nanoparticle. Sodium dodecyl sulfate (SDS) is used as the dispersant. Five different concentrations of nanofluids are configured using a two-step method. Droplet impacting behaviors are observed by high-speed imaging techniques. The other effects, i.e., the nanofluid particle volume fraction and the Weber number on droplet impact dynamics, are also systematically investigated. The results illustrate that the surface tension of the Al2O3 nanofluid increases with increased nanofluid concentrations. The surface tension of Al2O3 nanofluid with SDS is lower than that of DI water. And the increase in droplet impact velocity increases the spreading morphology. Nanofluid droplets exhibit spreading and equilibrium process when SDS is added. Furthermore, as the concentration of the nanofluid increases, the spreading process is inhibited. Whereas without SDS, the droplets undergo spreading, receding, and equilibrium processes. Moreover, there is no appreciable change in the impacting process with concentration increase. The empirical models of maximum spreading factor should be established without SDS and with SDS, respectively. This study can provide theoretical basis and specific guidance for experimental characterization of UAVs’ electronic devices based on the mechanism of nanofluid droplet impact on the wall.